Automação e melhoria do equipamento usado no cozimento do bacon - Maier, André Elias (2014)
The work consists of the realignment and improvement of a greenhouse, used to cook bacon in a refrigerator. The goal is to cook the bacon in a shorter time, but with better quality. It works based on temperature controllers, monitored by an operator. These temperature controllers were replaced by a programmable logic controller, and a soft-starter were installed to start the turbine engine. Some repairs will be also performed in its structure.